Role of Graded Compression Ultrasonography in Evaluation of Acute Appendicitis. - Shrestha, Mukunda Singh; Pant, Hom Prasad; Basnet, Shiv Bahadur; Khadka, Govinda Bhahadur; Shahi, Rajive Raj; Panta, Sujata (Medical Journal of Shree Birendra Hospital, 2015)
Introduction: Acute appendicitis is common surgical emergency which can lead to high morbidity and mortalityin absence of timely treatment. Ultrasonography (USG) is commonly used to diagnose appendicitis and excludeother intraabdominal pathology leading to right iliac fossa pain in emergency setting. We aimed to Þ nd out thediagnostic value of graded compression USG in suspected appendicitis cases. Methods: Altogether 107 patients with clinical impression of acute appendicitis were followed. Four caseswere excluded because of other diagnosis established in USG. Appendicitis was diagnosed by standard criteriasof inß ammed appendix by graded compression technique. Informations of 103 cases were recorded in proformawhich was later entered in SPSS and statistical calculations done. Results: Out of 103 cases followed, 93 had appendicitis. Of those, 46 cases only showed inß ammed anddistended appendix, others showed ancillary features only. Males were more affected 61(65.6%) than females.Sensitivity, speciÞ city, positive predictive value, negative predictive value and accuracy of ultrasound indetecting appendicitis were 98.9%,90%,98.9%,90% and 97.1% respectively. Conclusions: Graded compression ultrasonography is good investigation modality in assessement of suspectedacute appendicitis. doi: http://dx.doi.org/10.3126/mjsbh.v12i2.12929